1993
DOI: 10.5014/ajot.47.8.731
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Practice Issues Among Occupational Therapists in the Rural Northwest and the Rocky Mountain Regions

Abstract: The purpose of this study was to investigate factors that affected occupational therapy practice in the rural regions of the Rocky Mountains. It compared data from the Rocky Mountain region (Wyoming, Colorado, New Mexico, Utah, and Arizona) to a previous study of the Northwest region of Alaska, Idaho, Montana, and Washington and expanded on the Northwest study. Results indicated that the two areas were similar in their demographics and problems, including need for more occupational therapists. The results also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 3 publications
0
21
1
Order By: Relevance
“…It is likely that some therapists are more suited to the independent nature of rural practice. Kohler and Mayberry (1993) found that the most important attributes needed for rural practice were self-reliance and independence. Administrative skills may also be critical for success in an independent practice environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that some therapists are more suited to the independent nature of rural practice. Kohler and Mayberry (1993) found that the most important attributes needed for rural practice were self-reliance and independence. Administrative skills may also be critical for success in an independent practice environment.…”
Section: Discussionmentioning
confidence: 99%
“…These differences further challenge health human resource workforce planning and policy [14]. Hence, in order to improve access to health care services for people living in rural areas, we need to better understand key contextual factors in recruiting and retaining health providers to rural areas, in particular OTs and PTs [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Emphasis in the literature has largely been on issues related to recruitment rather than those related to retention. Low retention rates amongst health professionals impacts on the health of rural communities by creating difficulties in providing a consistent and reliable service (Huntley, 1995; Kohler & Mayberry, 1993). Studies in medicine and nursing suggest there are differences between factors affecting recruitment and those that affect retention.…”
Section: Introductionmentioning
confidence: 99%